Implementasi Perjanjian Waralaba Bisnis Lokal Dalam Bidang Pendidikan (Studi pada Bimbingan Belajar Smartgama Surakarta) - Fitriani, Anik, Septarina Budiwati, S.H, M.H.,C.N, Wardah Yuspin, S.H.,M.Kn.,Ph.D (2015)
One of the economic activities particularly in the field of trade are being given special attention from the government is a rapidly growing business franchise system. The study was conducted in order to determine the form and content of the franchise agreement on Smartgama course, to determine the execution of the franchise agreement on Smartgama course, to determine the constraints that occur in the process of the franchise agreement Smartgama course authors take the thesis with the title IMPLEMENTATION LOCAL BUSINESS FRANCHISE AGREEMENT IN THE FIELD OF EDUCATION (Studies in the Smartgama course) .This method used in this research is empirical juridical, because the study is the form and content of the franchise agreement at the Smartgama course. This type of research is descriptive because it is intended to explain the data in depth and detail. Data sources used include the primary and secondary data sources. The method of data collection is done in two stages, namely the collection of secondary data collected by the methods of literary study and dokimentasi with primary data collection through observation and discussion wawancara.Hasil research shows that the form and content of the franchise agreement at the Smartgama course a standard agreement that has been made or standardized by the ruling party is the franchisor and franchisee. Implementation of the franchise agreement in Smartgama course also been implemented. And there is a little problem that both parties are not consistent in the treaty. And constraints arising franchisee does not immediately pay the shortfall franchise fee when the already established agreement in full before the agreement is signed